MAKNA ETIS TRADISI DOA’ PENYULUNG PADA MASYARAKAT SUKU LEMBAK DI KELURAHAN SEMARANG KOTA BENGKULU - Fikriyadi Fikriyadi (Sekolah Pasca Sarjana IAIN Bengkulu, 2017)
This research is motivated by the reality in the field, there is a unique tradition done by the people of Lembak tribe in Semarang City Bengkulu City in welcoming the rice planting is the tradition of Do’a Penyulung. Researchers assume that this tradition has a religious message as well as a moral message. As the formulation of the problem in this research is the meaning of the ethical meaning of the traditions of Doul Pengulung to the people of Lembak tribe of Semarang City of Bengkulu City, how the procession of Doula Penyulung tradition in Lembur society of Semarang City of Bengkulu City, what is the meaning of symbols contained in the tradition of Do’a Penyulung In the community of Lembak urban village Semarang Bengkulu City. This research is generally aimed to know the procession of ethical meaning of Do’a Penyulung which is done annually to the people of Lembak tribe of Semarang City of Bengkulu City and to know the meaning of the symbol of Do’a Penyulung in Lembak tribe society in Semarang urban of Bengkulu City. For information in the field, the researcher uses field research type with qualitative approach. Based on the results of research and interviews conducted by researchers at the location of the research, the researchers can conclude, the ethical meaning of the tradition of Do’a Penyulung in the community of Lembak tribe in Semarang Village, Sungai Serut District Bengkulu City, raised both hands as high as Head, Head, register and head down, please permit to the chairman of the custom and the guests, right leg behind the slightly bent, local languages and national languages (Eigh Lembak Language and indonesian), wait From the chairman of customs and the organizers, the division of air siraman Which have been in prayer, gore ingredients in a jar or a particular container mixed one as much as 4 to 7 times, cover words received with regards and apologies, Pengulung includes, white and black sticky rice, Red Sugar, Coconut air and air Shrimp Acid, Jar or Bucket contains large Eros of Coconut shell, Yellow Cake, Seding leaves In and leaves of Mangosteen, leaves of Serai and Bamboo Aur yellow. All of them have a religious and sacred meaning for the people of Lembak tribe in Semarang City, Bengkulu City.